Financial Cryptography and Data Security 13th International Conference, FC 2009, Accra Beach, Barbados, February 23-26, 2009. Revised Selected Papers - Dingledine, Roger; Golle, Philippe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the 13th International Conference on Financial Cryptography and Data Security, FC 2009, held in Accra Beach, Barbados, in February 2009. The 20 revised full papers and 1 revised short papers presented together with 1 panel report and 1 keynote address were carefully reviewed and selected from 91 submissions. The papers are organized in topical sections on economics of information security, anonymity and privacy, private computation, authentication and identification, fraud detection and auctions.
Economics of Information Security I -- Mitigating Inadvertent Insider Threats with Incentives -- Deterring Online Advertising Fraud through Optimal Payment in Arrears -- Anonymity and Privacy I -- Privacy-Preserving Information Markets for Computing Statistical Data -- Achieving Privacy in a Federated Identity Management System -- Data Hemorrhages in the Health-Care Sector -- Private Computation -- Solving Linear Programs Using Multiparty Computation -- Private Intersection of Certified Sets -- Privacy-Preserving Classifier Learning -- Economics of Information Security II -- Investments and Trade-offs in the Economics of Information Security -- Blue versus Red: Towards a Model of Distributed Security Attacks -- Authentication and Identification -- Optimised to Fail: Card Readers for Online Banking -- Expecting the Unexpected: Towards Robust Credential Infrastructure -- Optical DNA -- Panel -- Passwords: If We$1 (Bre So Smart, Why Are We Still Using Them? -- Fraud Detection -- Defeating Cross-Site Request Forgery Attacks with Browser-Enforced Authenticity Protection -- Evil Searching: Compromise and Recompromise of Internet Hosts for Phishing -- Detecting Denial of Service Attacks in Tor -- Auctions -- Cryptographic Combinatorial Securities Exchanges -- Cryptographic Combinatorial Clock-Proxy Auctions -- Secure Multiparty Computation Goes Live -- Anonymity and Privacy II -- Coercion Resistant End-to-end Voting -- Relations Among Privacy Notions.s
Keywords: Computer science; Computer communication systems; Computer security; Data encryption (Computer science).; Algorithms; Computers and civilization; Management information systems; Computer Science; Data Encryption; Systems and Data Security; Management of Computing and Information Systems; Computers and Society; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Electronic books